Spaceborne LiDAR Systems: Evolution, Capabilities, and Challenges - Jan Bolcek; Mohamed Barakat A. Gibril; Jiří Veverka; Šimon Sloboda; Roman Maršálek; Tomáš Götthans (Sensors, 2025)
In the realm of earth observation and space exploration, LiDAR technology offers humanity insights into the dynamics of our planet and beyond. This paper reviews spaceborne LiDAR instruments with attention to their evolution, capabilities, and achievements. We focus on the high-level LiDAR instrument design, their components, and their operational parameters in contribution to the study of Earth. Through examining selected space missions, this work illustrates the role of LiDAR technology in our understanding of environmental and atmospheric phenomena. Furthermore, the paper looks ahead, discussing the ongoing development of advanced LiDAR technologies.